2002
DOI: 10.1182/blood-2002-02-0567
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor AN-9 has selective toxicity to acute leukemia and drug-resistant primary leukemia and cancer cell lines

Abstract: The novel prodrug of butyric acid, pivaloyloxymethyl butyrate (AN-9), a histone deacetylase inhibitor, shows great promise as an effective and relatively nontoxic anticancer agent for solid malignancies. However, little is known about its effects on hematopoietic malignancies. In this study, we show that 21 primary samples of acute leukemia were sensitive to the antiproliferative effects of AN-9, with a 50% inhibitory concentration (IC 50 ) of 45.8 ؎ 4.1 M. In colony-forming assays, primary T-cell acute lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…29,33,34 HL60/ADR, the doxorubicin-resistant clone of HL60 obtained by the transfection of the MDR-1 gene, was equally sensitive to pivaloyloxymethyl butylate-induced cytotoxicity as the parental cells. 35 Overall, these data suggest that several types of HDACIs can overcome the drug resistance of the cells expressing P-gp and/or MRP1. However, we revealed that FK228 and apicidin showed strong cross-resistance against the drug-resistant clones expressing P-gp and MRP1, which independently contributed to their resistance mechanisms.…”
Section: Discussionmentioning
confidence: 93%
“…29,33,34 HL60/ADR, the doxorubicin-resistant clone of HL60 obtained by the transfection of the MDR-1 gene, was equally sensitive to pivaloyloxymethyl butylate-induced cytotoxicity as the parental cells. 35 Overall, these data suggest that several types of HDACIs can overcome the drug resistance of the cells expressing P-gp and/or MRP1. However, we revealed that FK228 and apicidin showed strong cross-resistance against the drug-resistant clones expressing P-gp and MRP1, which independently contributed to their resistance mechanisms.…”
Section: Discussionmentioning
confidence: 93%
“…Butyrates have been under extensive clinical evaluation in both hematological malignancies and solid tumors. Butanoic acid or its prodrug pivaloyl oxymethyl butyrate (AN-9) is currently undergoing clinical trials after it showed 10-fold more potent activity than SB in leukemia tumor cell lines (Batova et al, 2002;Patnaik et al, 2002;. The antineoplastic activity of AN-9 stems from rapid hydrolysis and release of butyrate, permitting efficient delivery to subcellular targets (Zimra et al, 1997(Zimra et al, , 2000.…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%
“…While AN-9 displayed synergy with DNA-interacting agents, BA itself did not. 23 The synergistic effects between AN-9 and DNA-disrupting agents have been observed in murine monocytic leukemia cells and the combination of AN-9 with daunorubicin led to a significant increase in survival of mice inoculated with acute monocytic leukemia cells. 24 increased the level of doxorubicin-and mitoxantrone-DNA adducts and affected in a synergistic manner their antiproliferative activity in neuroblastoma and breast cell lines.…”
mentioning
confidence: 99%